Effectiveness of a virtual reality-based sensory stimulation intervention in preventing delirium in intensive care units: a randomised-controlled trial protocol - Yong Liu; Dan Luo; Taoxue Wen; Surui Liang; Mingxin He; Jinfei Tian (BMJ Open)
Introduction Delirium is a common acute cognitive impairment characterised by confusion, disorientation and attention deficits, particularly prevalent in intensive care unit (ICU) settings. Given its significant impact on patients, caregivers and healthcare resources, preventing delirium in patients in the ICU is of paramount importance. This is the first randomised-controlled trial designed to evaluate the effects of a virtual reality-based sensory stimulation intervention on preventing delirium in ICU patients.Methods and analysis We employed a paired randomisation method to match eligible participants based on a validated delirium risk scoring model for patients in the ICU. The study will commence in September 2024 and conclude in June 2026. A consecutive sample of 198 patients in the ICU admitted to the study setting will be recruited. Eligible participants will be randomly allocated to receive either virtual reality-based sensory stimulation in addition to usual care or usual care alone. The virtual reality-based sensory stimulation intervention will last for up to 14 days, with all interventions administered by a research team. We define delirium-free days over a 14-day period as the primary outcome. The secondary outcomes will include delirium incidence, duration and severity; patients’ psychological well-being (post-traumatic stress disorder, sleep quality and ICU memory); patients’ clinical outcomes and other outcomes (quality of life, independence and cognitive function). Data will be collected at baseline, post-intervention and 6 months post-intervention. Two independent t-tests or Wilcoxon-Mann-Whitney tests will be used for continuous variables, while χ2 or Fisher’s exact tests will be employed for categorical variables. The analysis will adhere to both the intention-to-treat and per-protocol principles. Additionally, mixed-effects models and subgroup analysis will be planned.Ethics and dissemination This protocol was approved by the Research Ethics Committee of Shenzhen Hospital of Southern Medical University (NYSZYYEC20230068). All participants or their family caregivers will provide written informed consent. Results will be disseminated through scientific publications, and presentations at local and international conferences.Trial registration number ClinicalTrials.gov NCT06153472. Trial registration date: 22 November 2023.